2019
DOI: 10.3390/met9060678
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Steel Coatings Deposited by Cold-Gas Spraying

Abstract: Cold-gas spray (CGS) deposition of amorphous steel coatings starting from a commercial feedstock powder containing boron, tungsten, and silicon was investigated. Microstructural characterization, carried out by X-ray diffraction (XRD), transmission electron microscopy, and backscattered electron diffraction (EBSD) analysis, confirmed the amorphous nature of deposited coatings. The amorphization phenomenon is related to high-strain/strain-rate deformation with shear instability caused by very high particle kine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 37 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Nowadays, CGS is accepted as a spray technique capable of depositing thick metal layers on different substrates at relatively low processing temperatures, maintaining the initial phase composition of different feedstock powders. Since the starting powders used in CGS remain in the solid state during the deposition, the most common defects of the high-temperature thermal spray processes, such phase transformation or oxidation, can be avoided [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, CGS is accepted as a spray technique capable of depositing thick metal layers on different substrates at relatively low processing temperatures, maintaining the initial phase composition of different feedstock powders. Since the starting powders used in CGS remain in the solid state during the deposition, the most common defects of the high-temperature thermal spray processes, such phase transformation or oxidation, can be avoided [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Such that smaller droplets at 100% helium produce higher cooling rate and less solidification time since heat transfer is faster in these situations [37]. Particles atomised in lower cooling rate exhibit higher crystalline fraction and on the other hand particle atomised in a higher cooling rate show a higher amorphous fraction [31].Amorphous metals exhibit excellent mechanical properties and have greater wear and corrosion resistance due to the absence of grain boundaries compare to crystalline materials [38][39][40]. Metal Cooling rate also has influence on the coating properties of powders such that increased cooling rates improves the coating properties of powder batch [41].…”
Section: Gas Atomisation (Ga)mentioning
confidence: 99%
“…It is reported that FeCrMoCB-Tm AAs have a high glass-forming ability [14][15][16][17][18][19] but high brittleness at room temperature, which greatly restricts their engineering applications. Thus, Fe-based AAs have been provided as powders for thermal spraying [20][21][22][23][24][25] against corrosion and wear for industrial applications [26][27][28].…”
Section: Introductionmentioning
confidence: 99%